SOCIAL DESIRABILITY OF PERSONALITY ITEMS AS A PREDICTOR OF ENDORSEMENT - A CROSS-CULTURAL-ANALYSIS - (:unkn) unknown (HELDREF PUBLICATIONS, 1993)
Earlier studies using specialized instruments confirmed a positive relation between a personality item's desirability and its endorsement outside North America, but allowed for few conclusions about the strength of the relationship in non-Western societies and offered no explanations for the observed correlations. In Study 1 of this investigation, university students from Turkey (a country rich in non-Western cultural elements) were found to be as likely as their U.S. counterparts to describe themselves in socially desirable terms. Furthermore, the strength of the relationship between desirability and endorsement did not depend on their level of exposure to the English language or to Western concepts. Study 2 indicated that socially desirable traits were also the most common among students in Turkey (paralleling results with U.S. samples), in support of desirable traits' prevalence as an explanation for the desirability-endorsement correlation.
Keywords: CONSTRUCT-VALIDITY